Local Wisdom Culinary At Kamu Kawan Lama Market In Denai Lama Tourism Village Deli Serdang District - Ngger P Cahyo Hutomo; Rahmat Darmawan; Muhammad Halfi Indra Syahputra (Kirana Publisher (KNPub), 2023)
Pasar Kamu Kawan Lama is a place where traders sell their culinary products every weekend. The Kamu Kawan Lama Market is located in the Denai Lama Tourism Village, Pantai Labu District, Deli Serdang Regency, North Sumatra Province. The many types of local food that are sold at Kamu Kawan Lama Market have made visitors curious to buy and enjoy the culinary offerings that are being sold. Local culinary wisdom that is offered at Kamu Kawan Lama Market is not neatly arranged according to the order of the dishes, so the majority of the food sold at Kamu Kawan Lama Market is dessert dishes or market snacks. The purpose of this research is to describe local wisdom-based culinary delights at Kamu Kawan Lama Market according to the procedure for serving food. The method used in this research is qualitative research, data collection is carried out in natural settings (natural conditions), primary data sources and data collection techniques involve participant observation , in-depth interviews , and documentation. . The analysis was carried out through an ethnographic approach with 3 analyses, namely domain, taxonomic, and componential analysis. The results of the research show that there is an imbalance in the sale of types of food dishes based on local wisdom, where the majority of the food sold is dessert or market snacks.